Evaluating and improving soil water and salinity stress response functions for root water uptake - Tianshu Wang; Yanqi Xu; Qiang Zuo; Jianchu Shi; Xun Wu; Lining Liu; Jiandong Sheng; Pingan Jiang; Alon Ben-Gal (Agricultural Water Management, 2023)
Many functions have been proposed to describe the response of root water uptake to water and/or salinity stresses. In practice, choosing a reliable stress response function is challenging, particularly when water and salinity stresses occur simultaneously. To explore and quantify the effects of soil water and salinity conditions, separately and combined, on root water uptake, two experiments culturing winter wheat in artificial climate chambers were conducted with various water and salinity levels. As the key index, plant water status was evaluated by: a) considering the relative position of water and salinity to roots; b) rectifying estimation of potential transpiration for stressed plants; c) excluding data during recovery periods dominated by the hysteresis process of historical stress; and d) quantifying the interaction between water and salinity stresses. Including only one fitting parameter and two water or salinity thresholds with clear physical meaning and available recommendations, concave-convex function could quantify the effects of water or salinity stress more accurately than the others, leading to more reliable estimation of relative transpiration rate (RMSE < 0.07, R2 > 0.91, MAE < 0.24). Under combined water-salinity stress conditions, neither an additive nor multiplicative approach was able to describe the interaction accurately. In addition to cumulative effect, by quantifying cross-adaptation effect with an exponential function, the multiplicative concave-convex functions significantly improved the estimation of relative transpiration rate for water- and salinity-stressed plants (RMSE < 0.08, R2 > 0.72, MAE < 0.28). Nevertheless, mechanisms underlying the interaction between water and salinity stresses are still unclear and should be further investigated. To avoid the hysteresis effect of historical stress, excluding data during recovery periods was helpful, but its quantitative characterization is also necessary for accurate simulation of root water uptake and should be further studied.